Role of Competent Authority in Strengthening of Radiation Safety Infrastructure for Nuclear Medicine Facilities in Bangladesh - Haider, Md Mofazzal; Nahar, Mehrun; Rahman, Mustafizur; Hossain, Amzad; Islam, Shahidul; Afroz, Shahana (Bangladesh Journal of Nuclear Medicine, 2016)
The peaceful use of radioactive sources/radiation generating equipment, in different areas, particularly in the medical sector contributes a lot in ensuring better quality treatment. The simple examples of beneficial application of radiation in the nuclear medicine are where radiation is being used for diagnosis and treatment of the patient. The misused or uncontrolled use of radiation can be a matter of serious concern for the human health in such kind of application. It is therefore essential to establish a stringent regulatory framework to avoid unwanted radiation exposure. According to International Atomic Energy Agency (IAEA) and national standard, every country should have an independent regulatory authority, which will maintain a process in order to control radiation related activities. In the present study, a comprehensive investigation is done on the nuclear medicine practices to assess the variations, which may happen in radiation safety situation due to the regulatory activities. The study is carried out including 5 nuclear medicine facilities, which are arbitrarily chosen, and their safety features are analyzed accordingly from the regulatory point of view. It is observed that at the outset of regulatory functions the radiation safety conditions of the facilities were not up to the level, as it was required by national and international standards. But the significant progress has been observed in the facilities within the couple of years after initiation of the regulatory program by the competent authority. Bangladesh J. Nuclear Med. 17(2): 125-129, July 2014